Fruit production under different environmental and management conditions of argan, Argania spinosa (L.) - Zunzunegui, M; Ain-Lhout, F; Jáuregui, J; Díaz Barradas, M C; Boutaleb, S; Álvarez-Cansino, L; Esquivias, M P (Journal of Arid Environments, 2010)
The study’s aim was to evaluate the effects of different management and environmental conditions on fruit and seed mass production of Argania spinosa, an endemic tree to Morocco that grows in arid and semiarid areas and is now undergoing a protracted regression due to overexploitation. Four study areas with different herbivory intensity, altitude and climatic conditions were selected. In each one the following measurements were carried out in 20 trees: tree and crown height, crown projection, trunk diameter, leaf area index, tree density, fruit production$m3 , number of fruits per tree, fruit, endocarp and kernel mass and seed size. The greatest fruit production and fruit size were found in populations with better climatic conditions, followed by the population under high human pressure. The lowest fruit production and fruit size were found in the population under the most severe climate conditions. Mean kernel mass was not affected by harsh climatic conditions or high human pressure, but when both stressing factors were combined all measured fruit traits were abated. Although A. spinosa is tolerant to high herbivory pressure, this perturbation induces a drastic decrease in fruit production. Managing plans addressing its reintroduction and/or maintenance should include a conservative strategy controlling herbivory
Keywords: herbivory; Kernel mass; leaf area index; Oil content; Oil production; seed mass